Peran Etika Kerja dan Motivasi Kerja Islami Bagi Kinerja Karyawan PT. Sun Life Financial Syariah Cabang Tangerang - Rizqi Pawzi Sukart; Oom Komariyah (STES Islamic Village, 2020)
The purpose of this study is to examine the effect of work ethics and Islamic motivation work on performance of the employees in PT. Sun Life Financial Syariah Tangerang-Banten. The sampling technique in this research uses purposive sampling method and to determine the number of respondents Slovin formula is used, Based on this formula the samples taken are 52 employees. This study is a quantitative descriptive method by using multiple regression method for analyzing the data and for data collection questionnaire is used in this research. The findings of this study is there is an positive impact of ethics work ethic and Islamic motivation work on employee performance at PT. Sun Life Financial Syariah, this can be explained through the coefficient of determination test of 50.25%. Simultaneous Test (F) and Partial Test (t) results show that work ethics (X1) and Islamic motivation work (X2) have a positive and significant effect on performance of employee (Y), where when Islamic work ethics increase at 1%, employee performance will increase amounted to 0.42% and when Islamic work motivation is increased by 1% then employee performance increases by 0.47%. Keywords :Islamic Work Ethics, Islamic Work Motivation, Employee Performance.